Embeddings and Widths of Weighted Sobolev Classes - Vasil’eva, Anastasia Andreevna (Eurasian Mathematical Journal, 2015)
In this paper, embedding theorems for reduced weighted Sobolev classes \( W^r_p,g(Ω) \) in Lebesgue spaces \( L_q,v(Ω) \) are obtained. Here weight functions have singularity at the origin and \( v otin L_q(Ω) \). For some special weight functions order estimates for Kolmogorov, Gelfand and linear widths are obtained.